New pOp/LhG4 vectors for stringent glucocorticoid-dependent transgene expression in Arabidopsis. - Craft, J; Samalova, M; Baroux, C; Townley, H; Martinez, A; Jepson, I; Tsiantis, M; Moore, I (2005)
To facilitate glucocorticoid-inducible transgene expression from the pOp promoter in Arabidopsis the ligand-binding domain of a rat glucocorticoid receptor (GR LBD) was fused to the amino terminus of the synthetic transcription factor LhG4 to generate LhGR-N. Fusions bearing the GR LBD at other positions in LhG4 exhibited incomplete repression or inefficient induction. LhGR-N was stringently repressed in the absence of exogenous glucocorticoid but was fully activated by addition of 2 microm dexamethasone which resulted in 1000-fold increase in GUS reporter activity. Half maximal induction was achieved with 0.2 microm dexamethasone. Reporter transcripts were detectable within 2 h of dexamethasone application and peaked 4-10 h later. Neither LhGR-N nor dexamethasone affected seedling development although ethanol retarded development when used as a solvent for dexamethasone. The efficiency of the pOp target promoter was improved 10- to 20-fold by incorporating six copies of the ideal lac operator with sufficient inter-operator spacing to allow simultaneous occupancy. Introduction of the TMV Omega sequence into the 5'UTR resulted in a further 10-fold increase in dexamethasone-inducible reporter activity and an increase in the induction factor to 10(4). Although promoters containing the TMV Omega sequence exhibited slightly increased basal expression levels in the absence of dexamethasone, stringent regulation of the cytokinin biosynthetic gene ipt was achieved with all promoters. Despite the severity of the induced ipt phenotypes, transcripts for the KNOX homoeodomain transcription factors BREVIPEDICELLUS and SHOOTMERISTEMLESS were not significantly increased within 48 h of dexamethasone application to seedlings.